HYDROXYLAPATITE OF BONE TISSUE: DYNAMICS OF CRYSTALLOCHEMICAL ALTERATIONS UPON OSTEOPOROSIS - A.A. Bibko; O.V. Bukharova; E.A. Kostrub; A.G. Miroshnichenko; M.V. Korovkin (Минералогия)
Bone tissue is a physiogenic organomineral aggregate consisting of organic (collagen, fats, sugars) and mineral (hydroxlyapatite) components. Osteoporosis is one of the most common bone diseases leading to disruption of bone tissue mineralization processes. To study the dynamics of changes in hydroxylapatite during osteoporosis, an experiment was conducted on laboratory animals with the simulation of systemic osteoporosis using ovariectomy (the surgical removal of an ovary or ovaries). The chemical composition of the mineral component of bone tissue was studied using electron microprobe analysis with further statistical processing of the results. The osteoporosis of bone tissue results in an increase in the content of isomorphic Mg, Al, and K in hydroxylapatite. A significant role of Al in the development of the disease was established using multivariate statistics methods. The X-ray diffraction revealed the increase in the unit cell parameters of hydroxylapatite with the osteoporosis progression. The results of IR spectroscopy showed the presence of a carbonate group in hydroxylapatite, the content of which decreases with disease.